Optimal primary care management of clinical osteoarthritis and joint pain in older people: a mixed-methods programme of systematic reviews, observational and qualitative studies, and randomised controlled trials - Elaine Hay; Krysia Dziedzic; Nadine Foster; George Peat; Danielle van der Windt; Bernadette Bartlam; Milisa Blagojevic-Bucknall; John Edwards; Emma Healey; Melanie Holden; Rhian Hughes; Clare Jinks; et al. (NIHR Journals Library, 2018)
Background: Osteoarthritis (OA) is the most common long-term condition managed in UK general practice. However, care is suboptimal despite evidence that primary care and community-based interventions can reduce OA pain and disability. Objectives: The overall aim was to improve primary care management of OA and the health of patients with OA. Four parallel linked workstreams aimed to (1) develop a health economic decision model for estimating the potential for cost-effective delivery of primary care OA interventions to improve population health, (2) develop and evaluate new health-care models for delivery of core treatments and support for self-management among primary care consulters with OA, and to investigate prioritisation and implementation of OA care among the public, patients, doctors, health-care professionals and NHS trusts, (3) determine the effectiveness of strategies to optimise specific components of core OA treatment using the example of exercise and (4) investigate the effect of interventions to tackle barriers to core OA treatment, using the example of comorbid anxiety and depression in persons with OA. Data sources: The North Staffordshire Osteoarthritis Project database, held by Keele University, was the source of data for secondary analyses in workstream 1. Methods: Workstream 1 used meta-analysis and synthesis of published evidence about effectiveness of primary care treatments, combined with secondary analysis of existing longitudinal population-based cohort data, to identify predictors of poor long-term outcome (prognostic factors) and design a health economic decision model to estimate cost-effectiveness of different hypothetical strategies for implementing optimal primary care for patients with OA. Workstream 2 used mixed methods to (1) develop and test a 'model OA consultation' for primary care health-care professionals (qualitative interviews, consensus, training and evaluation) and (2) evaluate the combined effect of a computerised 'pop-up' guideline for general practitioners (GPs) in the consultation and implementing the model OA consultation on practice and patient outcomes (parallel group intervention study). Workstream 3 developed and investigated in a randomised controlled trial (RCT) how to optimise the effect of exercise in persons with knee OA by tailoring it to the individual and improving adherence. Workstream 4 developed and investigated in a cluster RCT the extent to which screening patients for comorbid anxiety and depression can improve OA outcomes. Public and patient involvement included proposal development, project steering and analysis. An OA forum involved public, patient, health professional, social care and researcher representatives to debate the results and formulate proposals for wider implementation and dissemination. Results: This programme provides evidence (1) that economic modelling can be used in OA to extrapolate findings of cost-effectiveness beyond the short-term outcomes of clinical trials, (2) about ways of implementing support for self-management and models of optimal primary care informed by National Institute for Health and Care Excellence recommendations, including the beneficial effects of training in a model OA consultation on GP behaviour and of pop-up screens in GP consultations on the quality of prescribing, (3) against adding enhanced interventions to current effective physiotherapy-led exercise for knee OA and (4) against screening for anxiety and depression in patients with musculoskeletal pain as an addition to current best practice for OA. Conclusions: Implementation of evidence-based care for patients with OA is feasible in general practice and has an immediate impact on improving the quality of care delivered to patients. However, improved levels of quality of care, changes to current best practice physiotherapy and successful introduction of psychological screening, as achieved by this programme, did not substantially reduce patients' pain and disability. This poses important challenges for clinical practice and OA research. Limitations: The key limitation in this work is the lack of improvement in patient-reported pain and disability despite clear evidence of enhanced delivery of evidence-based care. Future work recommendations: (1) New thinking and research is needed into the achievable and desirable long-term goals of care for people with OA, (2) continuing investigation into the resources needed to properly implement clinical guidelines for management of OA as a long-term condition, such as regular monitoring to maintain exercise and physical activity and (3) new research to identify subgroups of patients with OA as a basis for stratified primary care including (i) those with good prognosis who can self-manage with minimal investigation or specialist treatment, (ii) those who will respond to, and benefit from, specific interventions in primary care, such as physiotherapy-led exercise, and (iii) develop research into effective identification and treatment of clinically important anxiety and depression in patients with OA and into the effects of pain management on psychological outcomes in patients with OA. Trial registration: Current Controlled Trials ISRCTN06984617, ISRCTN93634563 and ISRCTN40721988. Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grants for Applied Research Programme and will be published in full in Programme Grants for Applied Research Programme; Vol. 6, No. 4. See the NIHR Journals Library website for further project information.